PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA GAMBAR DAN CERITA PADA KELAS I UPT SPF SD NEGERI BARRANG LOMPO KECAMATAN SANGKARRANG KOTA MAKASSAR - Nurlindah; Andi Paida; Ratnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low initial reading skills of first-grade students, characterized by difficulty recognizing letters, slow comprehension, and a lack of confidence when reading. This study aimed to improve students' initial reading skills through the application of pictures and stories. The approach used was Classroom Action Research (CAR), implemented in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The subjects of this study were 32 first-grade students from the SPF Unit of Barrang Lompo Public Elementary School. The results showed significant improvement. In the initial test (pre-cycle), the average student score was only 68.8, with a completion percentage of 28%. In Cycle I, through the phonics and shared reading approach, students began to show progress, with an average score of 78 and a completion percentage of 34%. This improvement was supported by the reduction of cognitive load through visualization of the material (Wahyuningsih & Haryanto, 2021) and the application of constructivist learning (Hidayati, 2021). In Cycle II, the intervention focused on guided reading using thematic storytelling. As a result, the average student score jumped to 86, with a classical completion rate of 81%. Narrative engagement has been shown to stimulate students' imagination and emotions (Fitriani, 2021) and trigger intrinsic motivation (Sutrisno & Yuliana, 2022), leading to reading fluency and improved text comprehension. Therefore, it can be concluded that the interactive and contextual application of images and stories has proven effective in improving the beginning reading skills of first-grade elementary school students